HEPATITIS B, C AND HIV EXPOSURE ON NAT AND CLIA BLOOD EXAMINATION METHODS AT REGIONAL BLOOD CENTRE ABBOTTABAD - Irshad, Romana; Farooq, Umer; Shah, Tahir; Gul, Adeel; Badshah, Amir (Journal of Ayub Medical College Abbottabad, 2023)
Background: Blood transfusion is a lifesaving method in clinical emergencies. Despite various preventive measures, the spread of Hepatitis B, C and HIV remains a big issue in Pakistan. This study was done to describe transfusion transmitted diseases using NAT and CLIA techniques, on exposure to these viruses. Method: This study was conducted from 1st April to 25th August 2022. A descriptive study was done along with univariate analysis. The data was obtained from the regional blood centre in Abbottabad and it consists of reactive and non-reactive cases of NAT and CLIA in the sample size of 6233 donors. Data was collected from donors, and selected according to predefined criteria. Result: In 6233 samples, 53 were reactive for either Hepatitis B, C or HIV. Forty-seven were reactive with both CLIA and NAT. 6 were reactive with NAT only and 6107 were non-reactive. Conclusion: NAT yield detected in this study is 0.096%. (1:1039 donations). It implies that NAT should be the preferred method for screening in blood banks.